Descriptive analysis of quality features in the non-profit organisation (NPO) web site - Ibrahim, Muhamad Shamsul; Hassan, Md Salleh; Adzharuddin, Nor Azura; Shamshudeen, Rosya Izyanie (Faculty of Modern Languages and Communication, Universiti Putra Malaysia, 2018)
Web sitequality is important antecedents to create an excellentweb site to meet the NPO web site user expectation. This paper is adopting web site quality concept as suggested in Delone and McLean Model to measure the success of the NPO web site and the measurements for the web site quality elements were derived from the Diaz, Blasquez, Molina and Martin-Consuegra (2013) study. This research was conducted to identify the web site elements that are available in the selected NPOs web site. The status of the elements was analysed using descriptive analysis method. The findings of the study indicate the majority of the web sites show the high presence of information and system quality elements. Yet, for the web site service quality, it shows a lack of two ways communication elements. Evidently, there is a need to improve on web site effectiveness to market the NPOs idea. A few precautions measures related to internet speed and type of internet browsers were taken into consideration to minimise errors during the web site elements analysis which could cause a biased result. This study expects to improve the effectiveness of the NPOs web site via web site quality elements enhancement.